If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 7x + -3 = 60 Reorder the terms: -3 + 7x = 60 Solving -3 + 7x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7x = 60 + 3 Combine like terms: -3 + 3 = 0 0 + 7x = 60 + 3 7x = 60 + 3 Combine like terms: 60 + 3 = 63 7x = 63 Divide each side by '7'. x = 9 Simplifying x = 9

| 8x+17=6x+63 | | 11x+7=6x+27 | | 15x+8=10+14x | | 5x=4x+1 | | 11-10x=92-31x | | 10-y=9y-8 | | 12x-14=130 | | t+261=480 | | 13x=6x+28 | | 4x+3=3x+5 | | 3x+5=-4x-2 | | 7x+3=10x-6 | | 4.5(x-1)=-0.5x+20.5 | | 48-5x=4x+15 | | 5X^2+4X-4=0 | | 4c+5=21 | | 3(2x-1)=5(3x-15) | | 7x+21=5x+65 | | 10x-18=7x+3 | | 20-5x=40-4x | | x=8-12 | | 44=11j-11 | | 5x-87=2x-12 | | 4x+26=14x+74 | | 5x=90 | | 2P-1=13 | | 0.5(x-12)=0.5 | | 7z^2+9z+2=0 | | 90-4x=23x+18 | | 4x-3=12x-59 | | 5t+8=63 | | 8+5x=24+x | | 7x+54=-2x | | 9x+3x=18 | | 2a-32=2 | | 6x+11=110-5x | | 1y-7=8 | | 10+6x=70+x | | 2x-7=5-2x | | -26-3x=9-8x | | r-7=-4 | | 191-6x=6x+11 | | Y=4x^2+12x+8 | | s+7=-5 | | 4x+11=-49-8x | | h+5=15 | | -2y(5y+7)= | | 1-4x=19+5x | | -4.6x-1=-4.4+2 | | 2x^2+8x+1=0 | | -28-3x=4x+18 | | -3(t+1)=3 | | 5(x-1)-5=0 | | 96-2x=4x+18 | | 9-8x=174-43x | | 24-12=2(x-5) | | 146+2x+2x+26=172 | | 2(3c-1)-2=7c+9 | | -38-10=10x+22 | | 38+2x+125=x+163 | | -55z=55 | | 3x-6x+2=-4 | | 11-7x=68-28x | | 66-6x=30x+18 | | 144-6x=39x+24 |